2020
DOI: 10.7705/biomedica.4916
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the oncolytic potential of rotavirus on mouse myeloma cell line Sp2/0-Ag14

Abstract: Introduction: Cancer is the second leading cause of death in the United States, surpassed only by cardiovascular disease. However, cancer has now overtaken cardiovascular disease as the main cause of death in 12 countries in Western Europe. The burden of cancer is posing a major challenge to health care systems worldwide and demanding improvements in methods for cancer prevention, diagnosis, and treatment. Alternative and complementary strategies for orthodox surgery, radiotherapy, and chemotherapy need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…In the present study, we successfully adapted five rotavirus isolates to grow and induce cell death in colonic (Caco-2) tumor cells, which represent one of the most epidemiologically important human cancers. This remarkable property of the isolated rotaviruses makes them promising candidates for use as oncolytic agents, in the future [ 49 ]. Phylogenetic analysis revealed that the VP6, VP4, and VP7 segments of RVA144 isolated from Egyptian clinical specimens belong to G1P[8].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we successfully adapted five rotavirus isolates to grow and induce cell death in colonic (Caco-2) tumor cells, which represent one of the most epidemiologically important human cancers. This remarkable property of the isolated rotaviruses makes them promising candidates for use as oncolytic agents, in the future [ 49 ]. Phylogenetic analysis revealed that the VP6, VP4, and VP7 segments of RVA144 isolated from Egyptian clinical specimens belong to G1P[8].…”
Section: Discussionmentioning
confidence: 99%
“…Mostly, we focused on the promising combinations based on the published clinical data, rather than presenting all oncolytic virus variations. Nevertheless, many preclinical and clinical studies using vaccines (e.g., yellow fever 17D strain [ 231 ]), attenuated (Zika virus [ 232 ]) or cancer cell-adapted viruses (e.g., rotavirus [ 233 ]) are currently ongoing and demonstrating encouraging results [ 234 ]. Repurposing the virus vaccines for cancer immunotherapy is of particular interest since the pre-existing viral immunity may increase oncolytic effectiveness.…”
Section: Combination Therapies and Future Perspectivesmentioning
confidence: 99%
“…Moreover, from 12 hours post-infection, cells positive for viral antigens and negative for DAPI staining were observed, indicating the rupture and destruction of cellular DNA ( Fig 2A ). This mechanism of cell death, known as oncosis, has been associated with alterations in the transport and metabolism of calcium, leading to osmotic rupture, as previously reported in MA104 and Sp2 /0-Ag14 cancer cells [ 18 , 77 ].…”
Section: Discussionmentioning
confidence: 82%
“…These mechanisms are favored by conformational changes that depend on thiol-disulfide exchanges by protein disulfide isomerase (PDI). It has been shown that the infective capacity of RV is reduced by blocking its union with antibodies directed against these proteins [15][16][17][18][19][20][21][22][23][24][25][26][27][28].…”
Section: Gastric Cancermentioning
confidence: 99%